INNOVATIVE EDUCATION IN EDUCATION - EDUCATION (Archive of Conferences, 2020)
The article discusses the innovative approach and its priorities in the formation of democratic principles in the minds of young people in the process of teaching social disciplines in the education system of Uzbekistan and it is revealed on the example of the state youth policy